In situ, high-resolution evidence for the release of heavy metals from lake sediments during ice-covered and free periods - Zhu, Xiaoyan; Wu, Zhong; Han, Xuhang; Yang, Zihao; Dong, Xiangqian; Yuan, Yuxiang; Wang, Nannan; Qu, Zhi; Wang, Chunqing (Frontiers in Ecology and Evolution, 2024)
Heavy metal dynamics at the sediment-water interface (SWI) has attracted plenty of attention due to their meticulous depiction for metal sorption-release processes. However, little is known about their concentration, migration and release characteristics underneath the ice, especially at the millimeter scale. Here we investigated dynamics of labile As, Cd, Cu, Mn, Pb and Zn by the diffusive gradients in thin-films (DGT) technique during ice-covered and ice-free periods in the Lake Xingkai basin. The concentrations of metals were relatively high at the SWI and ranged for As: 0.001~13.42 g L−1, Cd: 0.01~0.45 g L−1, Cu: 0.001~2.75 g L−1, Mn: 5.31~2958.29 g L−1, Pb: 0.06~1.43 g L−1, and Zn: 2.92~112.96 g L−1. Particularly, concentration of Mn was extremely higher than other studies, possibly due to diagenetic process. Labile concentrations of heavy metals in January were significantly lower than those in May, suggesting that elevated temperatures lead to the release of heavy metals from the sediment to the overlying water. Based on the Fick's first law, the diffusive fluxes as a source of Mn (413.82-1163.25 mg·m-2·d-1) and As (3.53 -8.12 mg·m-2·d-1) indicated that heavy metals were released from sediments to the overlying water. While the diffusive fluxes as a sink of Zn (-1.80-(-2.36) mg·m-2·d-1) and Pb (-0.02-(-0.46) mg·m-2·d-1) to sediments. Redundancy Analysis (RDA) revealed that the main factors influencing the heavy metal migration were dissolved oxygen (45.6% of total explanation, P=0.01) in January, and water temperature (52.9%, P=0.006) in May. This study extends theoretical scope for understanding metal migration and release process, and provides valuable suggestions for lake management during the freezing period.